ETHYL ACETATE FRACTION OF GARCINIA MANGOSTANA-LINN PERICARP EXTRACT: ANTI-C.ALBICANS AND EPITHELIAL CYTOTOXICITY - Rahmayanti, Febrina; Suniarti, Dewi Fatma; Masud, Zainal Alim; Bachtiar, Boy M; Wimardhani, Yuniardini S; Subita, Gus Permana (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Candida spesies are commensal agent in oral, skin, and GIT environment, but when there is underlying predisposing condition in host, it causing candida infections. The increasing of antifungal resistance complicate patient management, therefore it is necessary to identify potential antifungal agents. Garcinia mangostana-Linn (GML) is a famous tropical fruits in Indonesia and other south-east Asia countries. This study was conducted to examine the antifungal activity of chromatographic coloumn ethyl acetate fraction of GML pericarp against C.albicans. GML was extracted with ethanol and fractionated with ethyl acetate. C.albicans ATCC 10231 was used in this study. Antifungal activities were expressed as viability of Candida albicans growth identification with MTT assay. There is no previous research that analyzes the antifungal effect of GML based on ethyl acetate fraction from the chromatographic fractionation technique, especially as anti-C.albicans. In this study, we also conducted an analysis of the cytotoxicity effect of ethyl acetate fraction on HaCaT cell line. The result of our study indicate that ethyl acetate fraction of GML pericarp extract have reduced the viability of C.albicans. There is a tendency of decrease in viability in line with the increase of concentration of fraction. As anti-C.albicans ethyl acetate fraction of GML pericarp extract has no cytotoxicity to HaCaT cell line. This result showed the ability of ethyl acetate fraction of GML extract changes the viability of C. albicans, but not toxic to HaCaT cell line. Â It may consider ethyl acetate fraction of GML pericarp extract as potent anti-C.albicans and promising adjuncts in oral health product.